Molecular Identification and Phenotypic Detection of Some Virulence Factors among Aeromonas hydrophila Isolated from Diarrhea Cases (Iraq) - Ilham A. Bunyan (Journal of Global Pharma Technology, 2018)
The present study included the detection of Aeromonas hydrophila in clinical samples were taken from patients suffering from diarrhea during the period from July (2017) to October (2017). A. hydrophila isolates which were diagnosed by four different methods (Culture media, biochemical tests, Api20E system and Polymerase chain reaction (PCR). Api20E kit was the important method for diagnosis of bacteria, which has led to isolate and, diagnosis of (35) isolates of A. hydrophila, but the PCR method of gene (16S rRNA) was more accurate method for diagnosis, which has led to isolate and diagnosis as (16) clinical isolates. The virulence factors of bacteria were detected, and showed that all isolates have ability to produce, heamolysin, protease, lipase, and capsule formation but have no ability to produce siderophores. In addition, A. hydrophila have the ability to adhere to uroepithelial cells of human and have strong biofilm formation.Keywords: Aeromonas hydrophila, 16S rRNA gene Capsule, Sidrophore, hemolysin, and Lipase.